Phylogeny of Lantana, Lippia, and related genera (Lantaneae: Verbenaceae) - Lu Irving, Patricia (2021)
Premise: Lantana and Lippia (Verbenaceae) are two large Linnean genera whose classification has been based on associated fruit traits: fleshy vs. dry fruits and one vs. two seed-bearing units. We reconstruct evolutionary relationships and the evolution of the two fruit traits to test the validity of these traits for classification. Methods: Previous studies of plastid DNA sequences provided limited resolution for this group. Consequently, seven nuclear loci, including ITS, ETS, and five PPR loci, were sequenced for 88 accessions of the Lantana/Lippia clade and three outgroups. Results: Neither Lantana nor Lippia is monophyletic. Burroughsia, Nashia, Phyla, and several Aloysia species are included within the clade comprising Lantana and Lippia. We provide a hypothesis for fruit evolution and biogeographic history in the group and their relevance for classification. Conclusions: Fleshy fruits evolved multiple times in the Lantana/Lippia clade and thus are not suitable taxonomic characters. Several sections of Lantana and Lippia and the small genera are monophyletic, but Lippia section Zappania is broadly paraphyletic, making circumscription of genera difficult. Lippia sect. Rhodolippia is a polyphyletic group characterized by convergence in showy bracts. Species of Lantana sect. Sarcolippia, previously transferred to Lippia, are not monophyletic. The clade originated and diversified in South America, with at least four expansions into both Central America and the Caribbean and two to Africa. The types species of Lantana and Lippia occur in small sister clades, rendering any taxonomy that retains either genus similar to its current circumscription impossible.